Purchasing strategy development: A multi-level review. Issue 2 (June 2015) - Hesping, Frank Henrik; Schiele, Holger
Abstract Is it reasonable to speak of 'the' purchasing strategy, or do different hierarchical levels of analysis need to be distinguished? A fragmented research field and a diverse set of understandings (including misunderstandings) of the scope of strategy development at various levels of analysis make a thorough discussion among researchers and practitioners difficult. Here, the state of the art in the purchasing strategy literature has been structured as a hierarchical framework fostering a multi-stage understanding of strategy development in purchasing. Research suggests that in purchasing, it is difficult to develop a single, all-encompassing strategy. To the contrary, a hierarchy of stages emerges when general strategy is disaggregated into executable and controllable activities: (1) firm strategy; (2) purchasing strategy as a particular functional strategy; (3) category strategies for the multitude of supply markets; (4) effectuation by a set of tactical sourcing levers and (5) strategies for each supplier within a sourcing category. In an effort to conceptualize the research field, this study extended existing stages of strategy development in purchasing and, for the first time, completely integrated sourcing categories and sourcing levers as levels of analysis.